Secondhand Smoke Exposure and Illness Severity Among Children Hospitalized with Pneumonia - Ahn, Anna (J Pediatr, 2015)
OBJECTIVE: To assess the relationship between secondhand smoke (SHS) exposure and disease severity among children hospitalized with community-acquired pneumonia (CAP). STUDY DESIGN: Children hospitalized with clinical and radiographic CAP were enrolled from January 1, 2010 through June 30, 2012 at three hospitals in Tennessee and Utah as part of the Centers for Disease Control and Prevention Etiology of Pneumonia in the Community (EPIC) study. Household SHS exposure was defined as the number of smokers in the child’s home. Outcomes included hospital length of stay, intensive care unit admission, and mechanical ventilation. Proportional hazards and logistic regression models were used to assess associations between SHS exposure and outcomes. All models were adjusted for age, sex, race/ethnicity, household education level, government insurance, comorbidities, enrollment site, year, and season. RESULTS: Of the 2219 included children, SHS exposure was reported in 785 (35.4%), including 325 (14.8%) with ≥2 smokers. Children exposed to ≥2 smokers had longer length of stay (median 70.4 vs. 64.4 hours; adjusted hazard ratio 0.85, 95% CI 0.75–0.97) and were more likely to receive intensive care (25.2% vs. 20.9%; adjusted odds ratio 1.44, 95% CI 1.05–1.96) but not mechanical ventilation compared with non-exposed children. Outcomes for children exposed to only one household smoker were similar to those for non-exposed children. CONCLUSIONS: Children hospitalized with CAP from households with ≥2 smokers had a longer length of stay and were more likely to require intensive care than children from households with no smokers, suggesting they experienced greater pneumonia severity.